حفريات علم الكلام ودور المتكلمين في الثقافة الإسلامية - Dedy Wahyudin (Ulumuna, 2009)
Kalam is included in genuine Islamic sciences. The birth of Kalam is affected by the dynamics of history of thought resulted from interaction between Islam and other religion and civilization. This paper is trying to capture the internal and external dynamics of the birth and development of the Kalam and also roles of mutakallimin (masters of Kalam) to maintain and develop Islam. Al-Qur’an internally gives Muslims the urge to think about the problems of divinity. The encouragement gained new momentum when it tangent to the internal political conflicts of the Muslims and reach maturity through its interaction with Greek philosophy. In the internal and external dynamics, the mutakallimin play a strategic role both in asserting the power of science, maintaining purity of Islamic teachings from attacks of other religions, and elaborating themes in Kalam that becomes an established Islamic science.